PTH-170 Five Year follow up of Patients with Asymptomatic Iron Deficiency Anaemia following Normal Investigations in a Nurse Led Protocol Driven Pathway. (4th June 2013) - Townsend, S A; Cheung, D; Ransford, R; Horne, E; Burdsall, J; Griffiths, H
Abstract : Introduction: Systematic investigation of patients with iron deficiency anaemia has been proven to yield a 12% diagnosis for colorectal cancer and 5% for coeliac disease 1 . Following publication of BSG guidelines, a nurse led protocol driven pathway was established at a district general hospital. We report the 5-year outcome of 122 patients with normal investigations entered onto this pathway and assess its efficacy in identifying GI pathology. This is the largest study to date in this field, and no other nurse led 5 year follow up studies have been published. Methods: Between 2001 and 2004, 271 cases of asymptomatic iron deficiency anaemia were referred to the pathway and 212 met the inclusion criteria. From initial investigations, 43% were diagnosed with an underlying cause of anaemia and we have now followed up the remaining 122 patients for a minimum of 5 years. Data collected at presentation included: haemoglobin, mean cell volume, ferritin, creatinine, iron-binding capacity, CRP, drug use (aspirin, clopidogrel, warfarin, NSAIDs), co-morbidities, smoking status, BMI, and the results of investigations carried out (gastroscopy, colonoscopy, barium enema). Iron supplementation was recorded and haemoglobin level at 3 months. Patients were divided into 2 groups: those that died or developed malignancy and those that were well at 5 years. The data was analysed for significant differences between the 2 groups and to identify risk factors for poor prognosis. Results: Analysis of primary and secondary care records generated outcome data of 97% (118) patients. 69% were female and 31% were male, mean age of 69 years. At 5 years, 20% had died or developed malignancy and 80% were alive and well. With the exception of diabetes, OR 0.24 (95%CI 0.1–0.8, p = 0.02), no other factors were found to be a significant risk factor for poor prognosis when the two groups were compared, including age, gender, haemoglobin level at presentation, persistent anaemia at 3 months, or other co-morbidities. Only 3 patients developed colonic malignancy; in all 3 patients the anaemia had resolved at 3 months. Two patients had diverticular disease only at initial barium enema but presented 4 years later with colorectal cancer. One patient declined lower GI investigation and presented with metastatic colon cancer on CT scanning at 1 year. No other GI cancers were diagnosed at 5 year follow up. Conclusion: This study demonstrates that this nurse led, protocol driven pathway is a highly effective and safe system for the exclusion of GI cancer with 5 years follow up and we would recommend implementation throughout the NHS. Disclosure of Interest: None Declared. Reference: Goddard A et al. Guidelines for the management of iron deficiency anaemia. GUT 2010; 60: 1309–1316.